Entomological aspects of Chagas' disease transmission in the domestic habitat, Argentina - SS Catalá; LB Crocco; A Muñoz; G Morales; I Paulone; E Giraldez; C Candioti; C Ripol
OBJECTIVE: To study the risk of Trypanosoma cruzi domestic transmission using an entomological index and to explore its relationship with household's characteristics and cultural aspects. METHODS: There were studied 158 households in an endemic area in Argentina. Each household was classified according to an entomological risk indicator (number of risky bites/human). A questionnaire was administered to evaluate risk factors among householders. RESULTS: Infested households showed a wide range of risk values (0 to 5 risky bites/human) with skewed distribution, a high frequency of lower values and few very high risk households. Of all collected Triatoma infestans, 44% had had human blood meals whereas 27% had had dogs or chickens blood meals. Having dogs and birds sharing room with humans increased the risk values. Tidy clean households had contributed significantly to lower risk values as a result of low vector density. The infested households showed a 24.3% correlation between time after insecticide application and the number of vectors. But there was no correlation between the time after insecticide application and T. infestans' infectivity. The statistical analysis showed a high correlation between current values of the entomological risk indicator and Trypanosoma cruzi seroprevalence in children. CONCLUSIONS: The risk of T. cruzi domestic transmission assessed using an entomological index show a correlation with children seroprevalence for Chagas' disease and householders' habits.